The error in using superposition to estimate pressure during multisite subsurface CO 2 storage - De,Simone S; Jackson,SJ; Krevor,S (Geophysical Research Letters, 2019)
Analytic pressure estimates for multisite CO2 injection are typically performed through the superposition of singlesite injection models. This is theoretically invalid for multiphase flow because of its nonlinearity. We quantify the error associated with the application of superposition in scenarios with sites located in a rectangular grid geometry. We show that the use of superposition results in overestimates of the pressure buildup, because it neglects the presence of multiple CO2 plumes, which increase the reservoir fluid mobility. The adoption of a dimensionless time scaled to the geometric average between the advective and diffusive characteristic times allows us to define a general model for the maximum error, which may be used to evaluate the validity of using superposition, or to correct the pressure estimates when errors are significant. This procedure can be applied to any analytical solution and advances the extension of singlewell models to scenarios of multiple injection sites.